Effects of Rhythmic Auditory Stimulation During Hemiplegic Arm Reaching in Individuals with Stroke: An Exploratory Study - Jung-ran Kim; Min-ye Jung; Eun-young Yoo; Ji-Hyuk Park; Sung-Hoon Kim; Jin Lee (SAGE Publishing, 2014)
Objective/Background: This study investigated the effects of rhythmic auditory stimulation (RAS) on muscle activity and elbow motion during arm reaching with hemiplegic arm in participants with stroke. Methods: Sixteen adults with stroke who resided in a community were recruited in this study. The RAS consisted of sound emitted from a digital metronome. While sitting upright in a chair, participants reached their arms towards a target (a switch on a table) both with and without RAS. The three-dimensional motion analysis system and surface electromyography system were used for measurements during the reaching tasks. Results: We found that RAS elicited better performance in reaching movements than those movements performed without RAS. RAS shortened the movement time (p = .002), reduced the change in acceleration (p = .001), increased the elbow extension range of motion (p = .001), increased muscle activation of the triceps brachii (p = .024), and reduced the co-contraction ratio (p = .015) of the affected arm. Conclusion: RAS might be a useful technique to facilitate improvements in motor function of the affected arm in patients with stroke.